English Teachers’ Utilization of the Merdeka Mengajar Platform South Kalimantan - Yasyir Fahmi Mubaraq; Yulieda Hermaniar; Yulida Khairunnisa; Dini Noor Arini (Institut Agama Islam Negeri (IAIN) Manado, 2026)
The integration of digital learning technologies has transformed educational practices worldwide, especially in the era of Kurikulum Merdeka in Indonesia. The Merdeka Mengajar Platform (MMP) was introduced by the Ministry of Education, Culture, Research, and Technology to enhance teachers’ pedagogical competence, provide professional learning materials, and facilitate innovative classroom practices. However, the extent to which Englist teachers in South Kalimantan utilize this platform remains underexplored. This study aimed at investigating the perception, frequency, and challenges associated with the use of Merdeka Mengajar Platform among English teachers. A qualitative survey designed was employed, and data were collected from 100 English teachers through a structured online questionnaire. The study examines teachers’ perspective using two frameworks: the Teachnology Acceptance Model (TAM) and the Technological Pedagogical Content Knowledge (TPACK) framework. The analysis revealed that 96.5% of respondents perceived the platform as beneficial, yet it needs policy interventions to improve accessibility, technical support, and motivational strategies. This research contributes to the understanding of technology integration in language education and offer empirical evidence for further refinement of the Merdeka Mengajar Platform.Keywords: Merdeka Mengajar Platform, Teacher Competence, Digital Pedagogy, English Educatio